HUBUNGAN KEMATANGAN EMOSI DENGAN KESEJAHTERAAN PSIKOLOGI PADA PASANGAN PERNIKAHAN DINI DI KECAMATAN TOMINI KABUPATEN BOLAANG MONGONDOW SELATAN - Lenny Syamsuddin; Sri Delvi Lamusu (program studi psikologi, 2023)
Emotional maturity is the tendency to respond to everything that happens with mature emotions according to the age level and norms that apply in society. Psychological well-being is one of the things that can affect the condition of an individual’s psychological well-being. This study aims to determine the relationship between emotional maturity and psychological well-being in early marriage couples. This research uses quantitative correlational research. The population in this study amounted to 62 people. Sampling using purposive sampling. This study uses the Product Moment test. From the results of this study, it was found that there was a positive relationship between emotional maturity and psychological well-being in Tomini District, with p = 0.12 (<0.05) and the correlation coefficient r = 0.288. The scale used is the emotional maturity scale and the psychological well-being scale. The higher the emotional maturity of the early married couple, the lower the psychological well-being of the early married couple and vice versa